Bioeconomy challenges and implementation: the European research organisations' perspective - Bergeret, Pascal; Svedin, Uno; Valceschini, Egizio (éditions Quae, 2018)
This book focuses on opportunities and challenges in implementing a bioeconomy strategy from a research and education perspective. It draws on contributions presented during the 30th EURAGRI annual conference held in Tartu (Estonia) in September 2016, as well as on other workshops organised as part of EURAGRI. EURAGRI is an informal gathering of EU research and higher education organisations and ministries interested in agri-food research. It works as a platform of exchange and discussion on topics of common interest pertaining to the organisation, orientation and outlook of agri-food research in Europe in connection with global changes.